2018
DOI: 10.6001/actamedica.v25i1.3698
|View full text |Cite
|
Sign up to set email alerts
|

Novel human genome variants associated with alcohol use disorders identified in a Lithuanian cohort

Abstract: Background.Alcohol use disorder (AUD) is a chronic relapsing brain disease characterized by compulsive alcohol use, loss of control over alcohol intake, and a negative emotional state when not using (1). Abusive alcohol consumption directly affects a person’s physical and psychological health and social life. The World Health Organization has shown that Lithuania is a leading country in pure alcohol consumption in the world (2). The aim of this study is to find novel genome variants that are associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…NALCN is widely expressed in the central nervous system and regulates neuronal excitability ( Lu et al, 2007 ). Several studies indicated that NALCN implicated in the ethanol responses of both animals and humans being ( Speca et al, 2010 ; Cochet-Bissuel et al, 2014 ; Wetherill et al, 2014 ; Baronas et al, 2018 ). One single nucleotide polymorphism (SNP) in NALCN has been found to strongly associate with the high risk of alcohol dependence ( Wetherill et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NALCN is widely expressed in the central nervous system and regulates neuronal excitability ( Lu et al, 2007 ). Several studies indicated that NALCN implicated in the ethanol responses of both animals and humans being ( Speca et al, 2010 ; Cochet-Bissuel et al, 2014 ; Wetherill et al, 2014 ; Baronas et al, 2018 ). One single nucleotide polymorphism (SNP) in NALCN has been found to strongly associate with the high risk of alcohol dependence ( Wetherill et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…NALCN modulates important functions such as locomotor behaviors ( Xie et al, 2013 ), respiratory rhythm ( Lu et al, 2007 ), and responsiveness to general anesthetics ( Jospin et al, 2007 ; Singaram et al, 2011 ; Ou et al, 2020 ; Yang et al, 2020 ). Previous studies reported that responses to ethanol was changed in NALCN mutations of both animals and humans ( Morgan and Sedensky, 1995 ; Speca et al, 2010 ; Wetherill et al, 2014 ; Baronas et al, 2018 ). The UNC79 heterozygous mice, which is an important auxiliary subunit of NALCN, exhibited acute hypersensitivity to and increased voluntary consumption of ethanol ( Speca et al, 2010 ), suggesting that NALCN may modulate the ethanol actions.…”
Section: Introductionmentioning
confidence: 99%